ANALYSİS AND CLASSİFİCATİON OF FREQUENT WRİTİNG ERRORS OF TURKİSH CYPRİOT UNİVERSİTY STUDENTS - Bostancı, Hanife (Revista Inclusiones, 2019)
This paper aims at analyzing and classifying frequent writing errors of Turkish Cypriot university students. Fifty-five English as a foriegn language (EFL) learners ranging from pre-intermediate to advanced proficiency levels, majoring in English Language and Literature at a private university in Northern Cyprus participated in this study. They were asked to write an essay about their summer holiday within the range of 100 to 300 words. After the identification of errors in students‟ writing, they were analyzed and categorized based on a model proposed by Kashavarz (2015). Inter-rater reliability was carried out for the analysis of errors. The linguistic analyses of the data showed that morphological errors were the most frequent produced in the participants‟ essays, followed by syntactic errors. The errors were also analyzed in the light of their contributory sources. The results showed that 208 (44.2%) of errors were interlingual, and 263 (55.8%) were developmental and intralingual. The findings have implications for syllabus designers and EFL teachers.